Using Adoptive Cellular Therapy for Localized Protein Secretion. Issue 2 (March 2021) - Evans, Alysa N.; Lin, Heather K.; Hossian, A. K. M. Nawshad; Rafiq, Sarwish
Abstract : Abstract: Redirection of T cell cytotoxicity by the chimeric antigen receptor (CAR) structure may not be sufficient for optimal antitumor function in the patient tumor microenvironment. Comodifying CAR T cells to secrete different classes of proteins can be used to optimize CAR T cell function, overcome suppressive signals, and/or alter the tumor microenvironment milieu. These modifications aim to improve initial responses to therapy and enhance the durability of response. Furthermore, CAR T cells can deliver these molecules locally to the tumor microenvironment, avoiding systemic distribution. This approach has been tested in preclinical models using a variety of different classes of agonistic and antagonistic proteins, and clinical trials are currently underway to assess efficacy in patients.